The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1128/aac.01396-09
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Intrapulmonary Pharmacokinetics and Pharmacodynamics of Posaconazole in Lung Transplant Recipients

Abstract: This prospective study evaluated the plasma and intrapulmonary pharmacokinetics and pharmacodynamics (PKPD) of posaconazole (POS) in lung transplant recipients. Twenty adult lung transplant patients were instructed to take a 400-mg POS oral suspension twice daily (BID) with a high-fat meal for a total of 14 doses. Pulmonary epithelial lining fluid (ELF) and alveolar cell (AC) samples were obtained via bronchoalveolar lavage, and blood samples were collected at the approximate time of bronchoscopy. POS concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 26 publications
5
35
0
2
Order By: Relevance
“…Similar findings were presented in a case report in which posaconazole accumulation was seen in the lung, liver, spleen, and kidney tissues of a renal transplant patient (8). Our finding was also in accordance with the findings that posaconazole was accumulated in alveolar macrophages and white blood cells in humans (9)(10)(11). A recently published study using an in vitro model of pulmonary epithelial cells found accumulation of posaconazole in cell membranes, especially in the endoplasmic reticulum, which persisted for at least 48 h after the removal of extracellular posaconazole (12,13).…”
supporting
confidence: 93%
“…Similar findings were presented in a case report in which posaconazole accumulation was seen in the lung, liver, spleen, and kidney tissues of a renal transplant patient (8). Our finding was also in accordance with the findings that posaconazole was accumulated in alveolar macrophages and white blood cells in humans (9)(10)(11). A recently published study using an in vitro model of pulmonary epithelial cells found accumulation of posaconazole in cell membranes, especially in the endoplasmic reticulum, which persisted for at least 48 h after the removal of extracellular posaconazole (12,13).…”
supporting
confidence: 93%
“…The calculated values of AUC last for LO and laninamivir in AM were 77 to 364 times higher than those for the drugs in ELF (Table 2). High-level accumulation in AM was also observed in several human BAL studies after the oral administration of antibiotics (3,5,8,18,22). The uptake mechanism of clarithromycin and azithromycin to AM was explored using cultured AM cells (NR8383 cells), and it was found that the uptake was partly reduced by ATP depletors (21).…”
Section: Discussionmentioning
confidence: 91%
“…Drug concentrations in epithelial lining fluid (ELF) and alveolar macrophages (AM) obtained from BAL fluid have been evaluated in healthy volunteers (1,5,8,18) as well as lung transplant recipients (3,22) and critically ill patients (9) to consider the efficacy of drugs against respiratory pathogens and the appropriate dosage regimens for antiinfective drugs. Among the neuraminidase inhibitors, the concentration of zanamivir in ELF after intravenous (i.v.)…”
mentioning
confidence: 99%
“…), the ELF/plasma concentration ratio was 11 (142) (57) and lung transplant patients (143). It has been suggested that high intracellular posaconazole concentrations may explain its effectiveness for prophylaxis ( Fig.…”
Section: Lungmentioning
confidence: 90%